Information System Analysis with Delone & Mclean Model Approach on Online Services of Perbanas Institute library - Suharyanto; Anggi Kwirndhany; Pamela Magdalena (Management Research Studies Journal, 2022)
The purpose of this study was to determine the effect of system quality, information quality, service quality on satisfaction, and the effect of satisfaction on net benefits using the DeLone & McLean model. The population in this study were Perbanas Institute students who had used the Online Library Service. The sampling technique was selected using purposive sampling and a sample of 100 people. Data retrieval using primary data with a questionnaire tool and the method used is SEM (Structural Equation Modeling) with the help of the SmartPLS application. The results showed that system quality, information quality and service quality had a positive and significant effect on user satisfaction, then user satisfaction had a positive and significant effect on net benefits. In the intervening, relationship system quality, information quality and service quality have a positive and significant effect on net benefits through user satisfaction.